Struktur dan Amanat Cerpen Arca Batu Karya IGG Djelantik Santha - Mira Apsari, Ni Wayan (Metta : Jurnal Ilmu Multidisiplin, 2022)
Balinese literature is one of the cultural heritages of Bali that still exists and is preserved to this day. Balinese literature consists of two parts: traditional Balinese literature and modern Balinese literature. The short story Arca Batu is a type of modern Balinese literature. This short story contains good advice or messages for life. The purpose of this study was to describe the structure and mandate of the short story Arca Batu by IGG Djelantik Santha. This study uses a qualitative method with primary data obtained from the short story Arca Batu. Data analysis using data reduction data, presentation and drawing conclusions. The results of the study found that the Arca Batu short story has an even structure, the Arca Batu short storyline uses a forward plot, the characters are divided into three, namely the main character, the supporting character, the secondary character, has three settings, namely place, time, and context. The short story of the Stone Arca with the theme of the pitutur perama. The message of Arca Batu hopes that readers will always help and love their families and other communities. This short story is written in basa kapara and has a religious message, a moral message, and a social message.